2020
DOI: 10.1002/jat.4062
|View full text |Cite
|
Sign up to set email alerts
|

Developmental neurotoxicity and toxic mechanisms induced by olaquindox in zebrafish

Abstract: Olaquindox (OLA) has been widely used as an animal feed additive in China for decades; however, its toxicity and toxic mechanisms have not been well investigated. In this study, the developmental neurotoxicity and toxic mechanisms of OLA were evaluated in zebrafish. Zebrafish embryos were exposed to different concentrations of OLA (25-1,000 mg/L) from 6 to 120 hours post fertilization (hpf). OLA exposure resulted in many abnormal phenotypes in zebrafish, including shortened body length, notochord degeneration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 78 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…Bdnf and gdnf genes increased the survival of dopaminergic neurons and promoted neuroprotection and nerve regeneration [39,40] . The protein encoded by mbp gene is important for maintaining myelin structure, and the loss of the myelin sheath leads to a variety of neurological diseases [41,42] . In this study, the expression of bdnf , gdnf and mbp , were downregulated by MPTP, and QLC prevented neuron loss, reduced inflammatory responses, and promoted the development of dopaminergic neurons.…”
Section: Resultsmentioning
confidence: 63%
“…Bdnf and gdnf genes increased the survival of dopaminergic neurons and promoted neuroprotection and nerve regeneration [39,40] . The protein encoded by mbp gene is important for maintaining myelin structure, and the loss of the myelin sheath leads to a variety of neurological diseases [41,42] . In this study, the expression of bdnf , gdnf and mbp , were downregulated by MPTP, and QLC prevented neuron loss, reduced inflammatory responses, and promoted the development of dopaminergic neurons.…”
Section: Resultsmentioning
confidence: 63%
“…The available chemotherapeutic drug-toxicity on FET study also reported that LPO could also induce apoptosis. 79 The AO study reveals that CP could cause 80 Inhibition of AChE activity signies the disruption of neurotransmission of CP in zebrash embryos/ larvae. Chemicals could cause neurotoxicity by binding and inducing phosphorylation on the serine hydroxyl group at the active site-esterication of AChE during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…AChE plays a significant role in embryonic neuronal and muscle development. 80 Inhibition of AChE activity signifies the disruption of neurotransmission of CP in zebrafish embryos/larvae. Chemicals could cause neurotoxicity by binding and inducing phosphorylation on the serine hydroxyl group at the active site-esterification of AChE during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish have a wide range of applications in ecotoxicology, pharmaceutical toxicology and developmental biology (Baraban et al, 2013; Y. Chen et al, 2021; Gu et al, 2021; Guo et al, 2021). Moreover, they are perfect animal models for observing the effects of drugs on embryo development, cardiogenesis, neurobehavior, and blood flow compared with other vertebrate models because they exhibit in vitro fertilization, in vitro development, body transparency and rapid growth and development of physiological functions (Chen et al, 2021; Serbanovic‐Canic et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the zebrafish genome has been sequenced and is highly similar to the human genome (Meng et al, 2020). Due to these obvious advantages, zebrafish have been widely used in drug toxicology and safety evaluation, ecotoxicology, chemical toxicity, new drug screening, a good model studied for human disease and developmental biology research in recent years (Baraban et al, 2013; Chen et al, 2021; Gu et al, 2021; Guo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%